A Review on Various Virtual Inertia Techniques for Distributed Generation - Singh, Deeksha; Seethalekshmi, K. (2020 International Conference on Electrical and Electronics Engineering (ICE3), 2020)
Increase in infiltration of Distributed Generation (DG) in the modern power system has opened up new challenges to system stability. The major challenge faced by the power system utility in the case of power electronic driven distributed generation is the absence of inertia in the system. This paper gives an insight into the idea of virtual inertia and also on the possibilities of introducing virtual inertia in power electronic devices tied distributed generation. It discusses the various topologies for emulating virtual inertia algorithm along with control strategies for implementing the algorithm. This paper also provides an inclusive review on the optimal amount and placement of the synthetic inertia in power system and emphasizes on research gaps in this vital area.